On-chip broadband nonreciprocal light storage - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (Nanophotonics, 2021)
Breaking the symmetry between forward- and backward-propagating optical modes is of fundamental scientific interest and enables crucial functionalities, such as isolators, circulators, and duplex communication systems. Although there has been progress in achieving optical isolation on-chip, integrated broadband nonreciprocal signal processing functionalities that enable transmitting and receiving via the same low-loss planar waveguide, without altering the frequency or mode of the signal, remain elusive. Here, we demonstrate a nonreciprocal delay scheme based on the unidirectional transfer of optical data pulses to acoustic waves in a chip-based integration platform. We experimentally demonstrate that this scheme is not impacted by simultaneously counterpropagating optical signals. Furthermore, we achieve a bandwidth more than an order of magnitude broader than the intrinsic optoacoustic linewidth, linear operation for a wide range of signal powers, and importantly, show that this scheme is wavelength preserving and avoids complicated multimode structures.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin scattering; integrated photonics; nonreciprocity; optical delay